O'Reilly Infrastructure & Ops Superstream Series Kubernetes - Newman, Sam; Hightower, Kelsey; Johnson, Jonathan; Körbes, Ellen; Liles, Bryan (O'Reilly Media, Incorporated, 2020)
Kubernetes radically changed the way applications are built and deployed in the cloud. Since its introduction in 2014, this container orchestrator has become one of the largest and most popular open source projects in the world. These sessions will show you how Kubernetes and container technology can help you achieve new levels of velocity, agility, reliability, and efficiency. What you'll learn-and how you can apply it Explore Kubernetes fundamentals Understand what to focus on during your first few weeks with Kubernetes Learn what's different in a VM-based world and what's remained largely the same See what's coming next for Kubernetes This Superstream is for you because ... You're a developer looking to get started with Kubernetes You use Kubernetes and want to learn more about what's coming next You want to become well-versed in the foundations and best practices of Kubernetes Prerequisites: Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Programming Kubernetes (book) Read Kubernetes Best Practices (book) Read Kubernetes Up and Running, second edition (book) Take Kubernetes in Three Weeks-Parts I and II (live online training courses with Jonathan Johnson).